2017
DOI: 10.1136/bmjopen-2016-015759
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective review of paediatric head injuries in Asia – a Pan Asian Trauma Outcomes Study (PATOS) collaboration

Abstract: ObjectiveWe aim to examine the mechanisms of head-injured children presenting to participating centres in the Pan Asian Trauma Outcomes Study (PATOS) and to evaluate the association between mechanism of injury and severe outcomes.Design and settingWe performed a retrospective review of medical records among emergency departments (EDs) of eight PATOS centres, from September 2014 – August 2015.ParticipantsWe included children <16 years old who presented within 24 hours of head injury and were admitted for observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
4
9
0
Order By: Relevance
“…However, the rate of decrease of injury-related complaints was slower than that of infection-related presentations, resulting in an increased proportion of children seen during lockdown who required procedures like manipulation for fractures and dislocations, or toilet and suture for lacerations. This reinforces the fact that the home is still the most common location for injuries [35], with the implication that we should consider upstream interventions involving home injury prevention education initiatives in future lockdown states. They also signal a need to allocate sufficient ED expertise, manpower and space to handle these injuries.…”
Section: Discussionsupporting
confidence: 56%
“…However, the rate of decrease of injury-related complaints was slower than that of infection-related presentations, resulting in an increased proportion of children seen during lockdown who required procedures like manipulation for fractures and dislocations, or toilet and suture for lacerations. This reinforces the fact that the home is still the most common location for injuries [35], with the implication that we should consider upstream interventions involving home injury prevention education initiatives in future lockdown states. They also signal a need to allocate sufficient ED expertise, manpower and space to handle these injuries.…”
Section: Discussionsupporting
confidence: 56%
“…Because we lack understanding on the current variation of TBI care across Asia, it is difficult to develop robust protocols that can promote multicenter trials in this region. A previous multicenter Asian study demonstrated important differences in TBI outcomes when countries were stratified by gross national income status (20).…”
mentioning
confidence: 99%
“…[18] There are several studies on this area published after the two systematic reviews. [12,19] Thus, in this systematic review, the evidence on the effect of pre-hospital intubation for patients (aged < 18) with severe TBI will be firstly comprehensively evaluated.…”
Section: Discussionmentioning
confidence: 99%